1991
DOI: 10.1111/j.1365-2648.1991.tb03440.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life: verification and use of a self‐ assessment scale in two patient populations

Abstract: The study described further evaluates the use of the Holmes & Dickerson linear analogue self-assessment scale in assessing the quality of life of both in-patients and out-patients undergoing radiotherapy for the treatment of malignant disease. The scale is shown to be feasible for use in both clinical settings and to be both reliable and valid. It is quick to use, easy to score and demonstrates marked differences between the patient populations. These differences are discussed and supported on clinical grounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…In this study patients on the gynaecological ward said more often than patients on the surgical ward that their situation during hospitalization had been taken into account. Earlier research has also concluded that different patient groups need and benefit from individualized care ( Sutcliffe & Holmes, 1991; Hallberg & Norberg, 1993; Hansen et al ., 1993 ; Werner et al ., 1994 ; Duffy, 1995; Cohen et al ., 1996 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study patients on the gynaecological ward said more often than patients on the surgical ward that their situation during hospitalization had been taken into account. Earlier research has also concluded that different patient groups need and benefit from individualized care ( Sutcliffe & Holmes, 1991; Hallberg & Norberg, 1993; Hansen et al ., 1993 ; Werner et al ., 1994 ; Duffy, 1995; Cohen et al ., 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different patient groups need and benefit from individualized care in different ways; this applies, for instance, to people with cancer ( Sutcliffe & Holmes, 1991), people with AIDS ( Hansen et al ., 1993 ), and physically restrained ( Werner et al ., 1994 ; Cohen et al ., 1996 ) or psychiatric patients ( Duffy, 1995). Elderly patients appear to be particularly susceptible to loss of individuality during hospitalization ( Kenny, 1990).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Physical and psychological needs Cox and Roghmann (1984), Smith (1991), Brown (1992Brown ( , 1994, Bendtsen and Bjurulf (1993), Hansen et al (1993), Berg et al (1994), Fonteyn and Cooper (1994), Oleson et al (1994), Thomas (1994), Werner et al (1994), Duffy (1995), Happ et al (1996) Abilities Sutcliffe and Holmes (1991), Brown (1992Brown ( , 1994, Burgener et al (1993) Health condition Smith (1991), Brown (1992), A Ê stedt-Kurki and Ha Èggan-Laitila (1992), Hansen et al (1993), Ha Èggman-Laitila (1994), Thomas (1994) Meaning of illness A Ê stedt-Kurki and Ha Èggman-Laitila (1992), Burgener et al (1993) Reaction or responses (illness and treatment) Cox and Roghmann (1984), Sutcliffe and Holmes (1991), A Ê stedt-Kurki and Ha Èggman-Laitila (1992), Burgener et al (1993), Hallberg and Norberg (1993), Brown (1994), Happ et al (1996) Feelings, sentiments Brown (1992, A Ê stedt-Kurki and Ha Èggman-Laitila (1992), Berg et al (1994), Ha Èggman-Laitila (1994), Happ et al (1996) Patient's personal life situation Earlier experiences Cox and Roghman (1984), A Ê stedt-Kurki and Ha Èggman-Laitila (1992), Allyne and Thomas (1994), Fonteyn and Cooper (1994) Life-situation in general (employment, ways of life, personal relationships) Brown (1992), Burgener et al (1993), Fonteyn and Cooper (1994), Happ et al (1996) …”
Section: Patient's Situationmentioning
confidence: 99%
“…It is indeed a commonplace that different patients need individual care, this applies, among others to older people (Kenny 1990, Warren 1992, Burgener et al 1993, Happ et al 1996, people with acquired immunode®ciency syndrome (AIDS) (Hansen et al 1993), cancer sufferers (Sutcliffe & Holmes 1991), physically restrained individuals (Werner et al 1994, Cohen et al 1996 and persons with dementia (Hallberg & Norberg 1993) or psychiatric problems (Duffy 1995). Its importance in nursing care has been seen when evaluated patients' are satis®ed with their care (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Also, that "I am sleeping well" loaded on the Phy instead of the Fnt subscale in the current study again seems more logical, as sleep quality is often grouped under the physical well-being domain in other QoL studies. 2,18,19 There is a close correspondence between physical status and function, so some shared variance is to be expected.…”
Section: Discussionmentioning
confidence: 99%